METHODOLOGICAL ASPECTS OF LANDSLIDE RISK ASSESSMENT WITHIN URBAN AREAS (CASE STUDY OF THE MODEL SITE "LYSA GORA", KYIV) - Ivanik, О.; Menshov, О.; Kravchenko, D.; Bondar, К.; Hadiatska, К.; Tustanovska, L.; Khomenko, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The integrated geological, geophysical, and GIS methods for the overall assessment of the geological hazards within the urbanized environment were considered. The principal gap in the understanding of the geologically hazardous areas in Ukraine (landslide, soil erosion, pollution, etc.) is the lack of information about the properties of rocks and soils as well as their interaction with the past and present natural and anthropogenic formation. The study area is the landslide activation territory of Lysa Gora in Kyiv, Ukraine (Golosiivsky district). The slope has the conditional stabilization. At the same time the landslides provide the real dangery to the infrastructure facilities. One of the examples is the deformation of the railway along the Stolychne Highway. Landslide susceptibility data have been collected. The proposed methodology consists of the geological, geophysical, thermography, and remote sensing. This methods provide the possibility for the monitoring of landslides at the model areas in Kyiv region. The electrical resistivity tomography at the Lysa Gora identified two local zones of activation of landslide displacements, which are located in the range of depths of 3-8 m from the ground surface. The random distribution of the soil magnetic susceptibility and frequency dependence of the magnetic susceptibility both on lateral and verical line (soil genetic horizons) identified the presence of the displacement, redistribution and deposition of the soil and underlaying rocks. All the mentioned factors are in the genetic relation to the soil erosion and initial landslides.
Keywords: landslide hazards; slope stability; geomorphology; electrical resistivity tomography; magnetic susceptibility; soil